(untitled) (Research, Society and Development, 2022)
The objective was to analyze the perception of nurses about the importance of hand hygiene for the prevention and control of infections in the Intensive Care Unit. This is a descriptive, exploratory, qualitative study. Six nurses working in the intensive care unit of a hospital and maternity hospital located in the Center-South region of Ceará participated in the study. Data collection took place from March to April 2022, using a semi-structured interview script as an instrument. Data were treated through Content Analysis. Through the analytical process, two thematic categories emerged: The Importance of Hand Hygiene for the Prevention of Infections Related to Health Care in the Intensive Care Unit and Safe Care: the frequency with which Hand Hygiene is performed within the Intensive Care Unit. It was evidenced that the practice of hand hygiene, under the perception of nurses, constitutes a strategy of paramount importance for the control and prevention of Infections Related to Health Care, as well as for self-protection within the scope of Intensive Care Units. Therefore, the usual practice of hand hygiene during the care provided to hospitalized patients contributes to the creation of a culture of patient safety and of the nursing professional who mediates care in that sector.